Floating Microspheres of Lafutidine: Formulation, Optimization, Characterization, in-vitro and in-vivo Floatability Studies Using Eudragit Grades - Kumar, Sunil; Tiwari, Abhishek; Goyal, Naveen (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim/Background: The objective behind this study was to develop a Microspheres of Lafuditine using central composite design for gastroretentive drug delivery. Materials and Methods: Gastroretentive Microspheres were prepared by Emulsion Solvent Evaporation method. The present investigation will study the effect of formulation variables (polymer concentration etc) on the floating behaviour and drug release characteristics for developing mathematical relationship between them and optimize the formulation with an aim to minimize onset of floatation, maximize the duration of floatation in stomach in order to achieve maximum bioavailability and therapeutic efficacy of selected drug. Microspheres were evaluated for shape, size, melting point, buoyancy time, floating capacity, % yield, swelling index, and in-vitro drug release and in-vivo kinetic studies. Results: Results showed that selected independent variables significantly affect the yield (66-85%), particle size (3.78-10.62 μm), buoyancy (42.68-95.75%), encapsulation efficiency (69.32–94.05%), and cumulative drug release from the microspheres (79.02-96.92%). The interface and quadratic terms were also affect the process variables, it can be said that to develop and optimize gastroretentive system of Lafuditine with central composite design (CCD) is a valuable second-degree design which is effective treatment of H. pylori mediated infection and also provides a base to localize the drug release in the gastric region. Conclusion: The gastroretentive floating Microparticulate system of Lafutidine will enhance the patient compliance and play a vital role in improving patient’s quality of life.
Keywords: Lafutidine; Eudragit; Central composite design; In-vitro drug release; Microparticulate system; Sodium bicarbonate